The Role of Career Women in Fulfilling Family Support in Bugis Society in Parepare City: Testing Gender and Social Fiqh - Oktaviani, Oktaviani; Rahmawati, Rahmawati; St. Nurhayati, St. Nurhayati (Al-Iftah: Journal of Islamic studies and society, 2020)
This study discusses the role of career women in fulfilling family livelihoods where women are more involved in supporting their families. The aims of this study are 1) to find out the dual roles of women as wives, mothers and women who work outside the home; 2) to find out the gender analysis of career women in fulfilling family income in the city of Parepare, and 3) to find out the analysis of social fiqh on career women in fulfilling the family income in the city of Parepare. This type of study is a field study and development (research and development) with a normative sociological approach. The primary data source is in the form of interview data from ten informants, namely, women who have jobs outside the home (career). The data from this study were analyzed descriptively qualitatively through validity tests and using triangulation techniques. The results of this study indicate that 1) The dual role of women as wives, mothers and women who work outside the home, wAnita as a wife is required to be loyal to her husband so that she can be a motivator for her husband's activities, women as housewives, who are responsible for the house and household management, manage everything in the household to improve the quality of life, women as career womenwho have a job outside the home and dwell in a certain field according to their expertise; 2) Gender analysis of career women who play a role in fulfilling family income, that men and women have the same rights to fulfill family income, and 3) Analysis of social fiqh on career women who play a role in fulfilling family livelihoods in the Bugis community in Parepare City, that wCareer women in the Islamic perspective are viewed from the position as creations that Islam provides a proper position and degree to women as well as the same status as men.